1H-MRS of hippocampus in patients after first manic episode. (February 2014) - Gigante, Alexandre Duarte; Lafer, Beny; Yatham, Lakshmi N.
Abstract Objectives. The investigation of the pathophysiology of bipolar disorder in patients at disease onset is a strategy to avoid the confounding effect of progression of disease or duration of treatment. Our purpose was to investigate in vivo neuronal metabolites in the hippocampus of bipolar disorder patients using proton magnetic resonance spectroscopy (1H-MRS) within 3 months after their first manic episode. Methods. Fifty-eight BD I patients meeting DSM-IV criteria following their first episode of mania and 27 healthy subjects were studied using 1H-MRS with a 3.0 T Philips Achieva scanner. Voxels with 30 × 15 × 15 mm were placed in the hippocampus on both sides of the brain and the signal was collected using a PRESS sequence with TE = 35 ms and TR = 2000 ms. Data analysis was performed using the LC Model software. Results. N-Acetyl-aspartate (NAA), choline (Cho), myo-inositol (mI), creatine (Cre) and glutamine + glutamate (Glx) levels were compared between the groups and no statistically significant differences were found. Conclusions. Our results suggest that early in the course of BD there are no alterations in neuronal metabolism or vulnerability in the hippocampus after the first manic episode.